Family's socioeconomic profile at birth and offspring mortality until midlife – The Northern Finland Birth Cohort 1966 study - Oura, Petteri; Ala-Mursula, Leena; Chamberlain, Andrew; Junno, Juho-Antti; Rissanen, Ina (Preventive medicine, 2022)
Family's socioeconomic profile collected prenatally is known to predict offspring mortality during early life, but it remains unclear whether it has the potential to predict offspring mortality until later life. In this study, 12,063 individuals belonging to the Northern Finland Birth Cohort 1966 were followed up from mid-pregnancy for 52 years (570,000 person years). Five distinct socioeconomic profiles were identified by latent class analysis based on mother's marital status, education, and occupation; father's occupation; number of family members; location of residence, room count, and utilities; and family's wealth. The classes were highest status families (15.4% of the population), small families (22.1%), larger families (15.4%), average wealth families (23.4%), and rural families (23.3%). Their associations to offspring mortality, via linkage to national offspring death records, were analysed by Cox regression, stratified by sex and age groups (0—19, 20—38 and 40–52 years). In total, mortality was 9.2% among male and 5.0% among female offspring. Risk for midlife mortality was higher among male offspring from larger families (hazard ratio 2.19, 95% confidence interval 1.32—3.63), average wealth families (1.66, 1.02—2.73) and rural families (1.63, 1.00—2.68), relative to offspring from highest status families. It seems that family's socioeconomic profile constructed prenatally has predictive value for midlife mortality among male offspring. Premature mortality of men and women seem to be two distinct phenomena with differing underlying factors as socioeconomic profile was not associated with mortality among female offspring. •Five distinct socioeconomic profiles of families were identified from general Finnish population in the 1960s.•Family's socioeconomic profile had predictive value for premature mortality in male offspring but not in female offspring.•Premature mortality of men and women seem to be two distinct phenomena with differing underlying socioeconomical factors.